Cloud manufacture-oriented resource integration management method - LIN XIANGYONG; TONG XIAOWEI; GUAN PIAOFANG; WANG QIUXIA; WANG LINZHU (2016)
The invention provides a cloud manufacture-oriented resource integration management method which comprises the steps of a first PC receiving manufacturing requirement description of a user, obtaining production resource information from a server according to the manufacturing requirement description, the first PC selecting production equipment or manufacture resources according to the obtained production information, the first PC adjusting machine manufacture parameters according to the input of the user and sending the machine manufacture parameters to the server, the server calling corresponding interfaces to complete the client request according to the received machine manufacture parameters and selected production equipment or manufacture resources. The invention relates to a data management method for a cloud manufacture system, and the method disclosed is compatible with various manufacture resources, thereby solving the problem of accessing of conventional processing equipment machine tools, knowledge,